Feminism-art-theory: an anthology 1968-2014 - Robinson, Hilary (Wiley Blackwell, 2015)
"Charting over 45 years of feminist debate on the significance of gender in the making and understanding of art, the long-anticipated new edition of Feminism-Art-Theory has been extensively updated and reworked. Completely revised, retaining only one-third of the texts of the earlier edition, with all other material being new inclusionsBrings together 88 revealing texts from North America, Europe and Australasia, juxtaposing writings from artists and activists with those of academicsEmbraces a broad range of threads and perspectives, from diverse national and global approaches, lesbian and queer theory, and postmodernism, to education and aestheticsIncludes many classic texts, but is particularly notable for its inclusion of rare and significant material not reprinted elsewhereProvides a uniquely flexible resource for study and research due to its scale and structure; each of the seven sections focuses on a specific area of debate, with texts arranged chronologically in order to show how issues and arguments developed over time"–Page 4 de la couverture.
Section: xix, 524 pages ; 26 cm
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; art engagé; art féministe; arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; lesbianisme; militance; postmodernisme; premier cycle; pédagogie; périodes historiques; queer; thématiques; théorie de l'art

Mais qu’est-ce qu’elles disent ? - Picq, Françoise (Libération des femmes: les années-mouvement, 1993)
Le 26 août 1970 à l'Arc de Triomphe, neuf femmes donnaient par une action symbolique le coup d'envoi d'un mouvement qui allait en une quinzaine d'années bouleverser profondément la société française.A partir de son expérience personnelle, de l'étude des écrits et des archives du Mouvement de libération des femmes, d'une enquête auprès des féministes de la première heure, Françoise Picq présente ici une histoire en trois temps : celui de la découverte, celui des contradictions, puis le temps de la réflexion et du bilan avec les années quatre-vingt.
Section: 380 pages ; 22 cm
Keywords: 1900-1999; 1970-1979; 1980-1989; approches et analyses; cours; discipline; droits des femmes*; europe; france; histoire et politique; inégalités; militance; mouvements de femmes*; patriarcat; postmodernisme; premier cycle; périodes historiques; régions géographiques; sciences humaines; soc1016; sociologie; systèmes d'oppressions; thématiques